STUDY THE EFFECT OF DIFFERENT LEVEL OF FRUCTOOLIGOSACCHARIDE (FOS) ON SOME BLOOD INDICES IN YOUNG COMMON CARP (CYPRINUS CARPIO L.) - Nasreen Abdulrahman; Vian Ahmed; Hawkar Ameen; Bakhan Hasan (Basrah Journal of Veterinary Research)
The present study was conducted to investigate the effects of dietaryfructooligosaccharide (FOS) on some blood indices of common carp Cyprinus carpio. Thefingerlings were adopted for 2 weeks and then reared in triplicate groups in 9 tanks (four fishper tank with average initial weights of (40 ± 3 g). Fish fed experimental diets containingdifferent levels of fructooligosaccharide (FOS); (7.5 and 10 g FOS/kg diet) to apparentsatiation twice a day for 10 weeks. The results showed significantly differences in Red bloodcell count (1012 cells/dl) in T2. Hemoglobin (g/dl) data was 11.597 in the control. The meancorpuscular hemoglobin (pg/cell) was 63.333 in control, 56.033 in T21 and 52.100 in T2;mean corpuscular hemoglobin concentration (g/l) was 28.100 in the T1; mean corpuscularvolume were (fL) 215.950 in control. White blood cell (109 cells/dl) data was (112.350) forcontrol; granulocyte % was (15.050) in control; Lymphocyte % was (82.750) for control;Platelets % was (56.500) in T2 and monocyte % was (13.300) in T1.